A Comparative Study of Attitude, Perception, Determinant and Effect of Increasing Cost of Healthcare on Health Seeking Behaviour of Academic Staff in Two Different Tertiary Institutions in Edo State, Nigeria (Western Journal of Medical and Biomedical Sciences, 2023)
The health seeking behaviour of a community determines how they use health services. Utilisation of health facilities can be influenced by different attitude, perceptions, determinants and effect of increasing cost of healthcare. The objective of this study was to compare attitude, perception, determinant and effect of increasing cost of healthcare of health seeking behaviour of academic staff in two different tertiary institutions in Edo state, Nigeria. Descriptive cross sectional design and multistage sampling techniques were employed for this study. Total respondents recruited for this study was 400. Questionnaires were used to collect the data. The data was analysed using the Statistical Package for Social Sciences software version 26.0 and the results were presented. Statistics test was deployed to test association between variables and set at p
Keywords: Attitude; Determinant; Edo State University Uzairue; Effect of increasing cost of healthcare; Health Seeking Behaviour; Federal Polytechnic Auchi; Perception